The effect of intermittent intraabdominal pressure elevations and low cardiac output on the femoral to carotid arterial blood pressure difference in piglets - Aksakal, Devrim; Wessel, Lucas; Kubiak, Rainer (Surgical endoscopy and other interventional techniques, 2016)
BACKGROUND: Our previous work in a laparoscopic setting in piglets revealed that the systolic femoral artery pressure was approximately 5 % higher than its carotid counterpart, whereas the mean and diastolic values showed no significant difference. This remained idem when the intraabdominal pressure (IAP) was gradually increased. In this study, we aimed to investigate the effect of (1) intermittent IAP elevations and (2) a low cardiac output (CO) on the blood pressure (BP) difference cranially (carotid artery) and caudally (femoral artery) of a capnoperitoneum (ΔP = P a fem-P a carot). METHODS: A total of twenty-two piglets (mean body weight 11.0 kg; range 8.9-13.3 kg) were studied. Of these, 14 underwent intermittent IAP elevations at 8 and 16 mmHg, and ΔP was measured. In another 8 piglets, a model of reduced CO was created by introducing an air embolism (2 ml/kg over 30 s) in the inferior caval vein (VCI) at 12 mmHg IAP to further assess the influence of this variable on ΔP. RESULTS: Systolic ΔP remained at a mean of 5.6 mmHg and was not significantly affected by insufflation or exsufflation up to an IAP of 16 mmHg. Diastolic and mean values showed no differences between P a carot and P a fem. P a fem, systol remained higher than its carotid counterpart as long as the cardiac index (CI) was above 1.5 l/min/m2, but fell significantly below P a carot, systol at a low CI. There was no CO-dependent effect on diastolic and mean ΔP. Repeated IAP elevations do not significantly influence ΔP. CONCLUSIONS: Intermittent IAP elevations do not significantly influence ΔP. Despite of a CO-dependent inversion of systolic ΔP, mean BP measurements at the leg during laparoscopy remain representative even at low CO values.